THE ROLE OF DISASTER INSURANCE IN MITIGATING THE RISK OF NON-PERFORMING LOANS IN INDONESIAN BANKING - Ratih Hastasari; Suharini (Yayasan Azam Kemajuan Rantau Anak Bengkalis, 2025)
Indonesia is highly vulnerable to natural disasters, which affect banking sector stability through increased credit risk, reflected in rising Non-Performing Loans (NPLs). Natural disasters disrupt borrowers’ cash flows, damage productive assets and loan collateral, and heighten default risk, particularly among micro, small, and medium enterprises and in disaster-prone regions. This study aims to analyze the role of disaster insurance in mitigating NPL dan NPF risk in Indonesia’s banking sector. Using a qualitative descriptive-analytical approach, the study relies on documentary analysis of reports from financial authorities, disaster management agencies, banking institutions, and relevant literature from 2017–2025. Content analysis is applied to examine disaster risk transmission and the effectiveness of disaster insurance as a risk transfer mechanism. The findings indicate that disaster insurance helps reduce NPL and NPF volatility by protecting collateral values and supporting post disaster cash flow recovery, although its effectiveness remains constrained by low insurance penetration. The study highlights the importance of strengthening disaster insurance to enhance financial system resilience.